Нова класифікація пасажирських перевезень залізничним транспортом - Чаркіна, Тетяна Юріївна; Григоренко, Андрій Дмитрович (Українська державна академія залізничного транспорту, Харків, 2024)
UKR: У статті досліджено індивідуальні потреби пасажирів залізничного транспорту, які необхідно враховувати під час планування перевезень. Авторами вперше здійснено докладну сегментацію та систематизацію споживачів послуг залізничного транспорту із застосуванням маркетингового підходу. Інтеграція запропонованої класифікації пасажирських потоків до наявних методик планування та організації перевезень дозволить більш ефективно використовувати наявні технічні, фінансові, трудові та інші ресурси пасажирської вертикалі залізничного транспорту.

ENG: Increasing competition in the passenger transportation market prompts carriers to quickly implement new measures to attract customers and search for innovative approaches to providing transportation services. Nowadays it is not enough just to transport a passenger from the point of departure to the point of destination. Travel conditions must correspond to a set of criteria individually formed in the passenger’s mind, according to which traveler will consider the trip to be of high quality and comfortable. Moreover, the trip must include an additional range of services that will be provided not only during, but also before and after the trip. Then passengers will be satisfied with the transportation and look forward to next trips. Railway transport, despite having such advantages as environmental friendliness, all-weather capability, safety, cost-effectiveness, cannot ignore this trend. In order to enhance competitiveness and capture a larger segment of the transportation market, the passenger division of JSC Ukrainian Railways must constantly improve, implement new measures to retain existing customers and attract new ones. The deterioration and shortage of railway passenger rolling stock, especially in the conditions of constant crises, does not allow to improve the quality and comfort of transportation at a sufficient pace. In such conditions, the carrier must use non-standard techniques and methods in passenger service and be more flexible to increase the attractiveness of railway passenger transportation. The authors proposed a new approach to the formation of a customer-oriented service in railway passenger transportation, which consists in taking into account the individual preferences of passengers, classifying and systematizing target consumer groups using a marketing approach. Integration of the proposed classification of railway passengers into the existing methods of planning and organizing transportation will allow more effective use of the available technical, financial, labor and other resources of the passenger division of railway transport. The introduction of a new approach to the provision of services will ensure that the needs of passengers are met and will bring additional revenue to Ukrzaliznytsia.
New Classification of Passenger Transport by Rail Transport
Т. Чаркіна: ORCID 0000-0001-6202-0910; А. Григоренко: ORCID 0000-0001-6050-4655
Keywords: залізничні пасажирські перевезення; класифікація пасажирських перевезень; маркетинговий підхід; індивідуальні потреби; клієнтоорієнтованість; railway passenger transportation; classification of passenger transport; marketing approach; individual preferences; customer focus; КЕМ; SOCIAL SCIENCES; SOCIAL SCIENCES::Business and economics